Multiplex PCR for the detection and identification of dairy bacteriophages in milk - del Rio, B. (2007)
Bacteriophage infections of starter lactic acid bacteria are a serious risk in the dairy industry. Phage infection can lead to slow lactic acid production or even the total failure of fermentation. The associated economic losses can be substantial. Rapid and sensitive methods are therefore required to detect and identify phages at all stages of the manufacture of fermented dairy products. This study describes a simple and rapid multiplex PCR method that, in a single reaction, detects the presence of bacteriophages infecting Streptococcus thermophilus and Lactobacillus delbrueckii, plus three genetically distinct ‘species’ of Lactococcus lactis phages commonly found in dairy plants (P335, 936 and c2). Available bacteriophage genome sequences were examined and the conserved regions used to design five pairs of primers, one for each of the above bacteriophage species. These primers were designed to generate specific fragments of different size depending on the species. Since this method can detect the above phages in untreated milk and can be easily incorporated into dairy industry routines, it might be readily used to earmark contaminated milk for use in processes that do not involve susceptible starter organisms or for use in those that involve phage-deactivating conditions.